CUSTOMER EXPERIENCE AND CUSTOMER ENGAGEMENT ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE (CASE STUDY AT MEDAN OIL PALM RESEARCH CENTER) - Indi Ade Fitri Koto; Sugiharto; Endang Sulistya Rini; Irma Zulhana Koto (CV. Radja Publika, 2024)
The Palm Oil Research Center (PPKS) is a company that provides quality seeds, research products on the upstream and downstream sides, and provides satisfying services and services to meet the needs of the people and stakeholders and supports the sustainability of the Indonesian palm oil industry . To support the sustainability of the industry, PPKS must maintain customer loyalty. In addition, customer satisfaction is also an important aspect that affects customer loyalty. The purpose of this study is to analyze the effect of customer experience and customer engagement on customer loyalty through customer satisfaction. This research was conducted at the Palm Oil Research Center (PPKS) with a sample of 125 respondents. The data were analyzed using descriptive analysis and path analysis with the Smart PLS application. The results show that directly customer experience has a positive and significant effect on customer satisfaction, customer engagement has a positive and significant effect on customer satisfaction, customer experience has a positive and significant effect on customer loyalty, customer engagement has a positive and significant effect on customer loyalty, and customer satisfaction have a positive and significant effect on customer loyalty. Indirectly, customer experience has a positive and significant effect on customer loyalty through customer satisfaction and customer engagement has a positive and significant effect on customer loyalty through customer satisfaction.